Impluse Hedonic Motives Influence on Buying through the Shopping Lifestyle - kurniantari, rizky; palupiningdyah, palupiningdyah (Management Analysis Journal, 2019)
Impulse buying behavior encourages consumers to shop unplanned without thinking of the benefit of the product purchased. Without dorongaan hedonic behavior or hedonic motives and lifestyle are high on the consumer, then the consumer will not do impulse buying. The purpose of this study to determine the direct and indirect effects of hedonic motives to impulse buying using variables shopping lifestyle as an intervening variable. The population in this study are all consumers Giant Tidar Magelang. Sampling using purposive sample with 115 the number of respondents. Data collection method used is the method of questionnaires and documentation. Analysis of data using path analysis path (path analysis) with the variables include hedonic motives, lifestyle shopping, impulse buying. The results showed that hedonic motives direct influence positively and significantly related to impulse buying. The result of path analysis showed that the lifestyle shopping able to mediate the association between hedonic motives to impulse buying. The conclusions of this study proved that hedonic motives direct influence positively and significantly related to impulse buying. Shopping lifestyle has a role as an intervening variable between hedonic motives to impulse buying. Suggestion for the company to further improve the facilities as well as the novelty of the atmosphere in the store. For further research to examine other retail types and can add new variables and or indicator to enrich the model and answer the problems and limitations of this research is going on.